Knowledge Management, Trust and Communication in the Era of Social Media - Joanna Paliszkiewicz (MDPI, 2020)
The article entitled "Selected Aspects of Evaluating Knowledge Management Quality in Contemporary Enterprises" broadens the understanding of knowledge management and estimates select aspects of knowledge management quality evaluations in modern enterprises from theoretical and practical perspectives. The seventh article aims to present the results of pilot studies on the four largest Information Communication Technology (ICT) companies' involvement in promoting the Sustainable Development Goals (SDGs) through social media. Studies examine which communication strategy is used by companies in social media. The primary purpose of the eighth article is to present the relationship between trust and knowledge sharing, taking into account the importance of this issue in the efficiency of doing business. The results showed that trust is vital in sharing knowledge and essential in achieving a high-performance efficiency level. The ninth article presents the impact of social media on consumer choices in tourism and tourist products' specificity. The study's main purpose was to indicate the most commonly used social media in selecting a tourist destination and implementing Generation Y's journey. The 10th article aims to identify the most critical purposes of using social media by responding to women's attitudes according to age and their respective countries' economic development. The research was done through an online survey in 2017-2018, followed by an analysis of eight countries' results. The article entitled "Integrated Question-Answering System for Natural Disaster Domains Based on Social Media Messages Posted at the Time of Disaster" presents the framework of a question-answering system that was developed using a Twitter dataset containing more than 9 million tweets compiled during the Osaka North Earthquake that occurred on 18 June 2018. The authors also study the structure of the questions posed and develop methods for classifying them into particular categories to find answers from the dataset using an ontology, word similarity, keyword frequency, and natural language processing. The book provides a theoretical and practical background related to trust, knowledge management, and communication in the era of social media. The editor believes that the collection of articles can be relevant to professionals, researchers, and students' needs. The authors try to diagnose the situation and show the new challenges and future directions in this area
Keywords: 650; digitalization; marketing activity; management; electronic tickets; joint-stock company “ Ukrzaliznytsia” electronic distribution channels; sales activity; smartphones; mobile applications; evaluation of mobile applications; usage of smartphones; digital media; empowerment; equality; Taiwan; computer games; creative companies; social media marketing; knowledge; knowledge management; knowledge management quality; communication; social media; strategy; sustainable development; corporate responsibility; ICT industry; trust; efficiency; tourism; knowledge sharing; Generation Y; Internet; tourist destinations; Polish social media users; social media in business; women; age preferences; emerging and developed economies; disaster information; question answering systems; question classification; Twitter analysis; natural language processing; neural disaster; word frequency; CSR reporting; financial performance; food industry; information sharing